Pengaruh Pengalaman Kerja dan Kompensasi terhadap Kinerja Karyawan LPD Desa Adat Mas - PRATIWI, KOMANG ANITA; DARMAWAN, DWI PUTRA; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Effect of Work Experience and Compensation on The Performance of LPD Desa Adat Mas Employees The success of the company is strongly influenced by the individual performance of its employees. Employee performance is important for every company as is LPD as a village-owned financial institution that supports village development. Employee performance is influenced by many factors including work experience and compensation. The purpose of this study was to determine the effect of work experience and compensation on the performance of LPD Desa Adat Mas employees and to analyze the effect of work experience on the performance of LPD Desa Adat Mas employees through compensation. Respondents in this study were 34 respondents. Data collection methods used are observation, interviews, documentation, and questionnaires. The data analysis technique used is quantitative analysis with a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results showed that work experience had no effect on the performance of LPD Desa Adat Mas employees, while compensation had an effect on the performance of LPD Desa Adat Mas employees. Work experience affects the performance of LPD Desa Adat Mas employees through compensation as a mediating variable. Compensation also fully mediates the effect of work experience on the performance of LPD Desa Adat Mas employees. Employee performance evaluation needs to be done regularly so that it can provide feedback to employees about the implementation of their work.